Knock on wood company : foldable dining set / Arif Azfar Azhar, Muhammad Nazri Mohd Salme & Mohd Afiq Syahmi Mohd Noor - Azhar, Arif Azfar; Mohd Salme, Muhammad Nazri; Mohd Noor, Mohd Afiq Syahmi (2017)
The project named 'Fordable Dining Set' was created and developed by our company which is KNOCK ON WOOD. The company was organized by 3 important members with a high intelligent prospect people who named Arif Azfar bin Azhar as General Manager and Marketing Manager, Muhammad Nazri bin Mohd Salme as Operational Manager and Mohd Afiq Syahmi bin Mohd Noor as Administration Manager and Financial Manager. The name KNOCK ON WOOD was created after a full commitment discussion among us and we were strongly agree about that name as it connected to our 'Wood Based' product. The meaning can be described by dividing them into two words which is KNOCK ON and WOOD. KNOCK ON word used as our company produced product that can be done by hardware tools such as hammer and nails which they have to be knocked and hit to combine two woods. In addition, we add another devices to improve the product. The word WOOD used as wood is the main medium for our product. Our tagline is "Don't Mess with Wood" as its carry a meaning with strong message. People nowadays always wanted a new thing with high maintenance but they did not realize the nature that useful to human kind. Wood can be recycled after being used and reduce wastage. Our company located at Lot 97,Jalan Lembah 18, Bandar Seri Alam, 81750 Masai, Johar. The product is created to help people make their own decision on where they want to sit and make some works as they can bring both wooden hair and wooden mini table anywhere. Besides, this product can also act as a very useful medium when spending time with family like picnic or family gathering.